Case Studies for School Leaders: Implementing the ISLLC Standards - Sharp, William; Walter, James K.; Sharp, Helen M. (Rowman & Littlefield Publishers, 1997)
Whatever your profession, a common base of knowledge and standards of performance are required for admission to practice. As an educator, while it is true that the individual states administer actual licensure procedures, they do so based on core standards established across states. These case studies, which cover a cross-section of these core values, are highly useful for people preparing to become educational leaders and for current practicing administrators.